2012
DOI: 10.1371/journal.pone.0031796
|View full text |Cite
|
Sign up to set email alerts
|

Independent Recruitment of a Flavin-Dependent Monooxygenase for Safe Accumulation of Sequestered Pyrrolizidine Alkaloids in Grasshoppers and Moths

Abstract: Several insect lineages have developed diverse strategies to sequester toxic pyrrolizidine alkaloids from food-plants for their own defense. Here, we show that in two highly divergent insect taxa, the hemimetabolous grasshoppers and the holometabolous butterflies, an almost identical strategy evolved independently for safe accumulation of pyrrolizidine alkaloids. This strategy involves a pyrrolizidine alkaloid N-oxygenase that transfers the pyrrolizidine alkaloids to their respective N-oxide, enabling the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
(47 reference statements)
1
21
0
1
Order By: Relevance
“…Three FMO genes were identified from S. exigua , the same number as in B. mori and H. armigera , according to the prediction using genomic data (Langel & Ober, ; Wang et al ., ). Phylogenetic analysis showed that there was no orthologous relationship between insect and mammalian FMOs (Naumann et al ., ), and the branching pattern of the tree displayed two obvious clusters of insect FMOs far separated from human FMOs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Three FMO genes were identified from S. exigua , the same number as in B. mori and H. armigera , according to the prediction using genomic data (Langel & Ober, ; Wang et al ., ). Phylogenetic analysis showed that there was no orthologous relationship between insect and mammalian FMOs (Naumann et al ., ), and the branching pattern of the tree displayed two obvious clusters of insect FMOs far separated from human FMOs.…”
Section: Discussionmentioning
confidence: 97%
“…However, the xenobiotic metabolism by insect FMOs is less studied, with only a few reports from Dr Ober's laboratory. Their research was mainly focused on the detoxification of host plant‐acquired PAs in insects (Naumann et al ., ; Sehlmeyer et al ., ; Langel & Ober, ; Wang et al ., ). PAs are typical plant secondary metabolites thought to play an important role as defensive chemicals in plants and in their adaptation to insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Wang et al. 2012). However, with our current dataset, we cannot yet ascertain if the proposed coevolutionary patterns observed in ceutorhynch weevils either simply support a “sequential evolution” model, where a single colonization of a new host plant group promoted diversification of the colonizing insect taxa, or if the inferred insect‐host associations may constitute a reciprocal system of coevolutionary radiations, as predicted by the “escape‐and‐radiate” model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the adaptive plasticity of metabolic enzymes involved in detoxication and digestion is a universal mechanism that is employed by herbivorous insects (Crossley, Chen, Groves, & Schoville, ; Despres, David, & Gallet, ; Heidel‐Fischer & Vogel, ). For the alkaloid resistance, enzymes, including ATP‐binding cassette (ABC) transporters, flavin‐dependent monooxygenase and sucrase showed evolutionary plasticity for alkaloid resistance (Wang, Beuerle, Timbilla, & Ober, ; Wang et al., ; Yu et al., ). Apart from the enzymes for detoxication and digestion, enzymes with other important physiological functions are also revealed here to undergo adaptive evolution to minimize the inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%